7 - Book Reviews: Diplomatie soldiering: Nigerian Foreign Policy, 1975-1979 , Garba, Joe Spectrum Books Ltd - Ibadan, Nigeria, 1987, d. 238.: by Andrew I. Ohwona - Andrew I. Ohwona, (Africa Development, 1989)
abstract